Spatially Fractionated Radiation Therapy in Sarcomas: A Large Single-Institution Experience - Safia K. Ahmed, MD; Ivy A. Petersen, MD; Michael P. Grams, PhD; Randi R. Finley, CMD; Michael G. Haddock, MD; Dawn Owen, MD, PhD (Advances in Radiation Oncology, 2024)
Purpose: Spatially fractionated radiation therapy (SFRT) is a recognized technique for enhancing tumor response in radioresistant and bulky tumors. We analyzed clinical and treatment outcomes in patients with bone and soft tissue sarcomas treated with modern SFRT techniques. Methods and Materials: Patients with metastatic or unresectable sarcoma treated with brass collimator, volumetric modulated arc therapy lattice, or proton SFRT from December 2019 to June 2022 were retrospectively reviewed. Consolidative external beam radiation therapy (EBRT) was delivered at the physician's discretion. Patient and treatment characteristics, treatment response (symptom improvement, local control, and imaging response), and toxicity data were collected. Results: The cohort consisted of 53 patients treated with 61 SFRT treatments. Median age at treatment was 60.0 years. The primary location was soft tissue in 46 courses (75%) and bone in 15 (25%). Fifty-three courses (87%) were treated for symptom relief. The most used SFRT technique was volumetric modulated arc therapy lattice (n = 52, 85%) to a dose of 20 Gy (n = 48, 79%; range, 16-20 Gy). EBRT was delivered post-SFRT in 55 (90%) treatment courses with a median time interval from SFRT to EBRT of 5 days (range, 0-14 days). Median physical EBRT dose and fractionation was 40 Gy (range, 9-73.5 Gy) and 10 fractions (range, 3-33 fractions). Median follow up was 7.4 months (range, 0.2-30 months). One-year overall survival and local control rates were 53% and 82%. Symptom relief was documented with 32 treatment courses (60%). Stable or partial response was observed with 47 treatment courses (90%). Four grade 3 to 4 acute and subacute toxicities were attributable to SFRT (8%). Conclusions: The current series is the largest to date documenting outcomes for SFRT in sarcomas. Our results suggest combined SFRT with EBRT is associated with a favorable toxicity profile and high rates of symptomatic and radiographic responses for metastatic or unresectable sarcomas.